Intraoperative monitoring of pelvic autonomic nerves during laparoscopic low anterior resection of rectal cancer - Zhou, Min-Wei (Cancer Manag Res, 2018)
BACKGROUND: Some patients with low rectal cancer experience anorectal and urogenital dysfunctions after surgery, which can influence the long-term quality of life. In this study, we aimed to protect nerve function in such scenarios by performing intraoperative monitoring of pelvic autonomic nerves (IMPAN). PATIENTS AND METHODS: We retrospectively investigated a series of 87 patients undergoing laparoscopic low anterior resection of rectal cancer. Nerve-sparing was evaluated both visually and electrophysiologically. IMPAN was performed by stimulating the pelvic autonomic nerves under processed electromyography of the internal anal sphincter. Urination, defecation, sexual function, and the quality of life were evaluated using validated and standardized questionnaires preoperatively and at follow-up, 12 months after surgery. RESULTS: Among a total of 87 patients (53 male and 34 female patients), IMPAN with simultaneous electromyography of the internal anal sphincter was performed in 58 (66.7%) patients. Bilateral positive IMPAN results for both measurements, indicating successfully confirmed pelvic autonomic nerve preservation, were obtained in 45 (51.7%) patients. No significant difference was found in terms of urogenital and anorectal functions between preoperative and postoperative patients with bilateral positive IMPAN (P>0.05). Compared to preoperative patients with IMPAN (unilateral) or without IMPAN, these patients exhibited higher International Prostate Symptom Score, a lower International Index of Erectile Function-5, and a lower Female Sexual Function Index score at 12 months postoperatively (P<0.05). CONCLUSION: IMPAN is an appropriate method with which to laparoscopically protect nerve function.